Complementary MRI for diagnosing fetal intracranial hemorrhage: a case series study - Luis A. Concha-Rebollar; Eduardo Torres-Olivas; Carla M. Garcia-Moreno; Beatriz Elias-Perez; Maria Barrera-Esparza; Nancy Sierra-Lozada; Sandra Acevedo-Gallegos (Journal of the Mexican Federation of Radiology and Imaging, 2023)
Introduction: Magnetic resonance imaging (MRI) provides high-resolution fetal anatomy that is recommended as a complementary examination when fetal ultrasound (US) identifies cerebral abnormalities. The aim of this study was to describe fetal MRI findings for diagnosing fetal intracranial hemorrhage (ICH) when nonspecific or inconclusive fetal cerebral US abnormalities are detected. Material and Methods: This case series included pregnant women referred to our center due to cerebral abnormalities detected by fetal US who were subsequently diagnosed with fetal ICH on MRI. Fetal ICH was identified based on signal intensity on T1- weighted image (WI) and T2-W1. Imaging age pattern of hemorrhagic lesions was described. Results: Among the 12 cases diagnosed with fetal ICH by fetal MRI, only three (25.0%) cases were detected by fetal US, while nine (75.0%) had nonspecific or inconclusive ultrasonographic findings. Ventriculomegaly was the most common finding on fetal US. Specific MRI T2 and T1-WI for the diagnosis of fetal ICH were identified in all 12 (100%) cases. Seven (58.4%) cases were classified as early subacute ICH with low-signal on T2-WI and high-signal on T1-WI. Four (33.3%) cases were classified as late subacute ICH, with hyperintense signal on both T2- and T1-WI. Only one case (8.3%) with acute fetal ICH showed a low-signal on T2- and isointense signal T1-WI. Conclusion: Fetal MRI is an accurate complementary tool for the diagnosis of fetal ICH when nonspecific or inconclusive abnormalities are detected by fetal US. This study is the first in Mexico to report fetal MRI findings for the prenatal diagnosis of fetal ICH.